Long‐term Outcomes of Stent Placement Inside the Bile Duct for Biliary Strictures After Living Donor Liver Transplantation. Issue 1 (20th August 2021) - Nishikawa, Yoshihiro; Uza, Norimitsu; Hata, Koichiro; Marui, Saiko; Kuwada, Takeshi; Matsumori, Tomoaki; Maruno, Takahisa; Shiokawa, Masahiro; Kuriyama, Katsutoshi; Kurita, Akira; Yazumi, Shujiro; Kodama, Yuzo; et al.
Abstract : In living donor liver transplantation (LDLT), anastomotic biliary stricture is a serious and refractory complication. In this study, we reviewed the transition of post‐LDLT anastomotic biliary strictures and evaluated long‐term outcomes of stent placement inside the bile duct, which is referred to as an "inside‐stent." Of 805 consecutive adult LDLT recipients in our institution (2000‐2018), we reviewed 639 patients with duct‐to‐duct biliary reconstruction and analyzed chronological changes of post‐LDLT biliary strictures. Moreover, we focused on the year 2006 when various surgical modifications were introduced and compared the details of post‐LDLT biliary strictures before and after 2006, especially focusing on the long‐term outcome of inside‐stent placement. The proportion of left lobe grafts had increased from 1.8% before 2005 to 39.3% after 2006 ( P < 0.001) to maximize the living donor safety. Overall, post‐LDLT anastomotic biliary strictures occurred in 21.3% of the patients with a median follow‐up period of 106.1 months, which was decreased from 32.6% before 2005 to 12.8% after 2006 ( P < 0.001). Anastomotic biliary strictures were less frequent in patients with left lobe grafts than with right lobe grafts (9.4% versus 25.4%; P < 0.001). The overall technical success rate of inside‐stent placement was 82.4%, with an improvement from 75.3% before 2005 up to 95.7% after 2006 ( P < 0.01). Furthermore, the stricture resolution rate remained high at approximately 90% throughout the observation period. Increased use of left lobe grafts with several surgical modifications significantly reduced post‐LDLT anastomotic biliary strictures, leading to favorable long‐term outcomes of inside‐stent placements for this condition.